Smoking and the risk of upper aero digestive tract cancers for men and women in the asia-pacific region - Ansary-Moghaddam, A.; Martiniuk, A.; Lam, T.; Jamrozik, K.; Tamakoshi, A.; Fang, X.; Suh, I.; Barzi, F.; Huxley, Rachel; Woodward, M. (Molecular Diversity Preservation International (MDPI), 2009)
Although smoking is an established causal factor for upper aero digestive tract cancer (UADTC), most of the evidence originates from the West. Thus, we analysed data from 455,409 subjects in the Asia Pacific Cohort Studies Collaboration. Over a median of around six years follow-up, 371 deaths from UADTC were observed- The hazard ratio (95% confidence interval) for current smokers, compared with those who had never smoked, was 2.36 (1.76 - 3.16), adjusted for age and alcohol drinking- Tobacco control policies are urgently required in Asia to prevent millions of deaths from UADTC that smoking will otherwise cause. © 2009 by the authors.